Pemilihan Karir Perempuan Sebagai Akuntan Pendidik Dalam Perspektif Simone de Beauvoir: Studi Kasus pada Akuntan Pendidik Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tanjungpura Pontianak - Soraya, Soraya; Farizi, Zulham Al (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2016)
Educators accountants have a significant role in the education world. This paper aims to gain a better understanding and in-depth information on the aspects that make up the women"™s options for a career as an accountant educators. Further goal is to explaining the selection of women"™s careers as educators accountant in perspective Simone de Beauvoir. This paper used a qualitative approach. Researcher also conducted narrative researchers through in-depth interviews to the 7 (seven) women in the Department of Accounting Faculty of Economics and Business, University of Tanjungpura Pontianak. From the interviews, founded are six aspects that make up the women"™s options for a career as an accountant educators. These six aspect are the job opportunity (vacancies), time work flexibility, family background, meeting many people (students), childhood dream, and knowledge sharing. From these six aspect of the career choice, job opportunity (vacancies) and time flexibility aspect are the most disclosed widely aspect in choosing a career as an accountant educators. In addition, Simone de Beauvoir perspective can not explain the selection of women"™s careers as educators accountant.